Estrategias de marketing digital en redes sociales para la promoción del restaurante de comida rápida la Carreta Fast Food en la ciudad de Guaranda, provincia Bolívar, año 2024 - Panchana Castillo, Mercedes Yamileth (2024)
The execution of the research project called “Digital Marketing Strategies in Social Networks for the Promotion of the Fast Food Restaurant La Carreta Fast Food in the city of Guaranda, Bolivar Province, Year 2024”, the general objective is to develop Digital Marketing strategies in social networks for the promotion of the fast food restaurant La Carreta Fast Food in the city of Guaranda. The hypothesis indicates that digital marketing strategies in social networks will improve the promotion of the fast food restaurant la Carreta Fast Food in this way the methodology was used where the explorative and descriptive research is made known. The results obtained showed that digital marketing strategies help in a positive way for the fast food restaurant, the conclusions state that both strengths and weaknesses were identified, highlighting the lack of presence in social networks which negatively impacts the visibility of the brand, as a recommendation is given to continue implementing digital marketing strategies in social networks for the promotion of La Carreta and continue strengthening the brand within the market.